Business process change : a guide for business managers and BPM and six sigma professionals - Harmon, Paul, 1942- (Business Process Change., 2007)
Every company wants to improve the way it does business, to produce goods and services more efficiently, and to increase profits. Nonprofit organizations are also concerned with efficiency, productivity, and with achieving the goals they set for themselves. Every manager understands that achieving these goals is part of his or her job. In this balanced treatment of the field of business process change, Paul Harmon offers concepts, methods, cases for all aspects and phases of successful business process improvement. Updated and added for this edition are coverage of business process management systems, business rules, enterprise architectures and frameworks (SCOR), and more content on Six Sigma and Lean--in addition to new coverage of performance metrics. * Extensive revision and update to the successful BPM book, addressing the growing interest in Business Process Management Systems, and the integration of process redesign and Six Sigma concerns. * The best first book on business process, the most up-to-date book to read to learn how all the different process elements fit together. * Presents a methodology based on the best practices available that can be tailored for specific needs and that maintains a focus on the human aspects of process redesign. * Offers all new detailed case studies showing how these methods are implemented.